(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدف البحث إلى الكشف عن التأثيرات النفسية والاجتماعية الناجمة عن الضغوطات المهنية التي يعاني منها المعلمون في مدارس الحلقة الأولى من التعليم الأساسي . ومعرفة الترابط بين المعلمين حول هذه التأثيرات تبعاً لمتغيري (الوضع العائلي وسنوات الخبرة ). اعتمد البحث المنهج الوصفي، من خلال استخدام استبانة لجمع المعلومات والبيانات الضرورية للبحث. تضمّنت الاستبانة (33) بنداً لضغوطات مهنة التعليم، منها (19) بنداً عن التأثيرات النفسية و( 14) بنداً عن التأثيرات الاجتماعية، وطبّقت الاستبانة على عينة من معلمي الحلقة الأولى من مدارس التعليم الأساسي في مدينة دمشق، بلغت ( 100 ) معلم ومعلّمة . أظهرت نتائج البحث ما يلي : 1-أنّ هناك تقارباً بين آراء أفراد العينة مجتمعين حول التأثيرات النفسيّة والاجتماعية ، التي تنجم عن ضغوطات مهنة التعليم ، ولا سيّما الـتأثيرات النفسيّة :(ضعف الدافعية للتحسين ، وعدم مناسبة مهنة التعليم ، وهي لا تحقّق الطموحات) .وكذلك التأثيرات الاجتماعية : (تجنّب الحديث مع الزملاء، الراتب لا يناسب الوضع الاجتماعي ، عدم تعاون الزملاء لتطوير العمل). 2- وجود علاقة ارتباط إيجابية بين آراء أفراد العينة، حول التأثيرات النفسية والاجتماعية التي تنجم عن ضغوطات مهنة التعليم، بحسب متغيّر الوضع العائلي (متزوج، وغير متزوّج) معامل ارتباط سبيرمان (69ر91 – 33ر79). 3- وجود علاقة ارتباط إيجابية بين آراء أفراد العينة، حول التأثيرات النفسية التي تنجم عن ضغوطات مهنة التعليم، بحسب متغيّر سنوات الخبرة (عشر سنوات وأقل، أكثر من عشر سنوات)، معامل ارتباط سبيرمان (63ر72 ). 4- وجود علاقة ارتباط سلبية بين آراء أفراد العينة ، حول التأثيرات الاجتماعية التي تنجم عن ضغوطات مهنة التعليم، بحسب متغيّر سنوات الخبرة (عشر سنوات وأقل،أكثر من عشر سنوات)، معامل ارتباط سبيرمان (88ر11) The research aims to make known the psychology and sociology effects of stresses of teaching professional on teachers in first episode from basic learning , and known the correlation between teachers according to the variables (family position , and teaching experience in learning). The research adopted the descriptive method, by the questionnaire it has been used to collect the facts and the data from sample includes(100 ) teachers in Damascus city schools. The questionnaire includes( 33 ) term , ( 19) from them about psychology effects and( 14) from them about social effects . The result of study were finding : There are identical between opinions of all teachers about psychology and social effects of stresses of learning vocation, especially, psychology effects (weakness of motive to improvement, non suit vocational leering and no carry of aspirants ) . so sociology effects ( avoid talk with colleagues , the salary not suit for social statute, and not co-operation between colleagues for development. There are positive correlation relationship between opinions of sample members about psychology and social effects, according to variable of tamily position(married, non married)Coefficient Correlation ( 91,69-79V33). There are positive correlation relationship between opinions of sample members about psychology effects, according to variable of experience years. (ten year and less, more than ten years ), Coefficient Correlation ( 72,63). There are negative correlation relationship between opinions of sample members about social effects, according to variable of experience years. (ten year and less, more than ten years), Coefficient Correlation ( 11,88).